Predicting how much a consumer is willing to pay for a bottle of wine: a preliminary study - Alonso, Hugo (2022)
The wine industry is an important business sector, generating billions in annual revenue. In the last year, there were several lockdowns due to the COVID-19 pandemic and wine consumption at home has increased. This paper considers the problem of predicting how much a consumer is willing to pay for a bottle of wine to drink at home, in a regular occasion. As far as we know, this is the first study on the subject. The problem is treated as a classification task and several prediction models, based on artificial neural networks, support vector machines and decisions trees, are proposed and compared.